STRATEGI PENGEMBANGAN PERTANIAN ORGANIK TERPADU PADA CV GESTY SINO ORGANIK (GS ORGANIK) DESA PENFUI TIMUR, KECAMATAN KUPANG TENGAH, KABUPATEN KUPANG - Seprisen Laibahas Laibahas; Fidelis Klau; Kudji Herewila (Buletin Ilmiah Impas, 2020)
ABSTRACT This research aims to know the bigness of integrated organic farming income and an appropriate strategy in the development of integrated organic farming on CV Gesty Sino Organic (Organic GS.). Source and technic of data collecting in this research are interviews to get primary data using questionnaires, while secondary data collected using relating literature with this research.Data which collected, arranged according to the objective to be achieved, namely to know the bigness of integrated organic farming income namely difference between the revenue (TR) – total cost of farming (TC) and to formulate appropriate strategies in the development of integrated organic farming using SWOT analysis. From the results of research it is known that: 1. Total income earned on CV GS Organic on April 2019 is Rp19.423.837. 2.Some strategies that can be done in the development of integrated organic farming are: a)increasing the integrated organic farming in a larger scale to meet the needs of consumers and feet up revenue with other farm lobbies as well as applying modern farming techniques that are studied in Australia at CV GS Organic .b) necessary to increase cattle maintenance on the other land which not be cultivated yet on seling purpose. c) necessary cadres forming of labor which understand well about integrated organic farming to manage the garden when the owners of CV GS Organic went out of the region. d) manages the farming that is run by continuing to follow every technology development, increasing the farming of CV GS Organic on agrotourism scale because of the various crops, livestock and fish on conducted farming.